(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to analyze and synthesize scientific findings related to the management of school table tennis clubs, focusing on three main components: the club’s organizational structure, the role of the coach, and parental involvement. This study employed a literature review design, examining 15 articles published between 2015 and 2024 that were relevant to the context of school sports development. The analysis revealed that a clear and documented organizational structure is the primary foundation for creating an effective and sustainable training program. The role of the coach emerged as the most influential variable, requiring coaches to master not only the technical aspects of the game but also pedagogical skills, interpersonal communication skills, and the provision of constructive feedback. Other findings revealed that parental involvement significantly contributes to student motivation, commitment to training, and retention in club activities. Adaptive parental support has been shown to strengthen students’ emotional connection to the sport and increase participation in extracurricular activities. This study emphasizes the importance of integrating these three components in establishing a holistic and effective coaching ecosystem. In conclusion, managing school table tennis clubs requires a collaborative management model based on the school, coach, and parent as a strategy to improve the quality of sports development in formal educational settings.